Risk Factors According to Ethnicity among Coronary Artery Disease Patients - Bista, Mamta; Gaudel, Saroj; Gartoulla, Kshitij; Lamichhane, Sunita Dhakal (International Journal of Atharva, 2025)
Background: This study was conducted out to evaluate the risk factors according to ethnicity among coronary artery disease patients. Methods: A retrospective study was conducted at Shahid Gangalal National Heart Centre (SGNHC) in Kathmandu, Nepal. Data from the hospital’s database, which included 837 patients, was utilized to collect information on the disease over a one-year period. Statistical analysis was performed using SPSS version 20. Results: The most common preexisting risk factors were Hypertension (65%), smoking (56.4%) and dyslipidemia (32.1%). More than 70% of Muslims, Newars and Dalits among the recruited population had the history of hypertension. More than 55% of Brahmin/ Chhetris, Newars, Dalits, Madhesi other castes people were current or previous smokers. More than 25% of the people from all six ethnic groups had Dyslipidemia and it was statistically significant (p=0.000) with the ethnicity among the sample population. The Newar (4.8%) and Tarai/Madhesi (4.8%) ethnic groups exhibited the highest prevalence of four or more simultaneous risk factors, while the Brahmin/Chhetris and Janajatis had the lowest rates (0.8% and 0%, respectively). Additionally, the absence of conventional risk factors was most commonly observed among Brahmin/Chhetris (9.6%) and Dalits (3.3%). The relation between the 4 or more risk factors and Ethnicity was statistically significant (P value=0.009). Conclusions: Hypertension, smoking, and dyslipidemia emerged as the most prevalent preexisting risk factors among the studied population, with hypertension affecting 65% and smoking impacting 56.4% of participants. Notably, over 70% of Muslims, Newars, and Dalits reported a history of hypertension, while more than 55% of various ethnic groups were identified as current or former smokers. Dyslipidemia was present in over 25% of individuals across all six ethnic groups, demonstrating a statistically significant correlation with ethnicity. Four or more simultaneous risk factors were most common among the Newar and Tarai/Madhesi groups, whereas they were least common among the Brahmin/Chhetris and Janajatis. Interestingly, a lack of conventional risk factors was most common among Brahmin/Chhetris (9.6%) and Dalits (3.3%), highlighting important ethnic disparities in health risk profiles within the population.